2019
DOI: 10.1007/s13197-019-03664-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brazilian green propolis on microorganism contaminants of surface of Gorgonzola-type cheese

Abstract: Blue cheeses are susceptible to yeast and bacterial growth on their surface, which causes spoilage during ripening process and the formation of slime. The dairy industry frequently control the proliferation of undesirable microorganisms with natamycin and high salt concentration. The green propolis is a complex of substances that presents antimicrobial properties with great potential as preservative in the food industry. The aims of the present study were to identify the mesophilic aerobic microorganisms prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
3
12
0
2
Order By: Relevance
“…The higher antibacterial activity of the Ardahan propolis is probably related to its higher sugar content ( 83 ). Antimicrobial activity of propolis is also associated with its phenolic, flavonoid, and ester content, according to some reports ( 84 , 85 ), which may explain the difference in antibacterial activity between the Ardahan and Erzurum propolis samples in our study but not the absence of antifungal effect in either, even though one Brazilian ( 86 ) and one Turkish study ( 87 ) reported a significant antifungal effect. One study from Chile ( 88 ) showed different phenolic/flavonoid content and antimicrobial activities of propolis from six locations but found no clear correlation between the two.…”
Section: Resultssupporting
confidence: 55%
“…The higher antibacterial activity of the Ardahan propolis is probably related to its higher sugar content ( 83 ). Antimicrobial activity of propolis is also associated with its phenolic, flavonoid, and ester content, according to some reports ( 84 , 85 ), which may explain the difference in antibacterial activity between the Ardahan and Erzurum propolis samples in our study but not the absence of antifungal effect in either, even though one Brazilian ( 86 ) and one Turkish study ( 87 ) reported a significant antifungal effect. One study from Chile ( 88 ) showed different phenolic/flavonoid content and antimicrobial activities of propolis from six locations but found no clear correlation between the two.…”
Section: Resultssupporting
confidence: 55%
“…The evaluation of green propolis ethanol extract (EEP) ( Apis mallifera ) as a cheese preservative was motivated by its tremendous in vitro bactericide and fungicide effects against several yeasts and bacteria ( Staphylococcus , Bacillus , Enterococcus , Corynebacterium , and Proteus spp.) by MFC/MIC ranging from 1 to 2.2 and MBC/MIC equal 2, respectively, with the most sensitive being S. cerevisiae (MFC = 0.63%) and the most resistant fungi being Candida parapsilosis (MFC = 5%) [ 74 ]. Thus, a dosage from 1.25% ( w / w ) EEP was capable of completely inhibiting Staphylococcus saprophyticus , and the Staphylococcus equorum count after 24–28 h, 37 °C, as well as from 1.25% or 2.5% ( w / w ) completely inhibited Yarrowia lipolytica or Debaryomyces hansenii after 48–72 h (for yeasts) at 37 °C on the surface of Gorgonzola-type cheese.…”
Section: Green Preservatives By Natural Antimicrobials As Cheese Preservativementioning
confidence: 99%
“…Thus, a dosage from 1.25% ( w / w ) EEP was capable of completely inhibiting Staphylococcus saprophyticus , and the Staphylococcus equorum count after 24–28 h, 37 °C, as well as from 1.25% or 2.5% ( w / w ) completely inhibited Yarrowia lipolytica or Debaryomyces hansenii after 48–72 h (for yeasts) at 37 °C on the surface of Gorgonzola-type cheese. However, only 5% EPP was suggested as a promising concentration once it showed a sensory quality (i.e., taste, odor, and overall) similar to the control cheese, and 10% EPP was worse than the control [ 74 ].…”
Section: Green Preservatives By Natural Antimicrobials As Cheese Preservativementioning
confidence: 99%
“…Its inhibitory effect is mainly attributed to inhibition of protein synthesis and certain functions of cell membranes (Kahramanoglu et al, 2020;Cruz et al, 2021). Correa et al (2019) indicated that propolis mainly inhibits aerobic microorganisms, while different bacterial species have different inhibitory concentrations. Furthermore, Kahramanoglu et al (2020) found that the propolis extract has a significant inhibitory effect on important genes in the biosynthetic pathway of aflatoxin at the concentration of 125 µg mL −1 .…”
Section: Propolismentioning
confidence: 99%
“…Correa et al . (2019) indicated that propolis mainly inhibits aerobic microorganisms, while different bacterial species have different inhibitory concentrations. Furthermore, Kahramanoglu et al .…”
Section: Biopreservatives From Different Sources and Their Applicatio...mentioning
confidence: 99%